Intervention on Externalizing Problems of Undercontrolled Personality Types in Primary School Students - Yu, Yongjin; Yang, Lizhu; Sun, Yan; Jin, Chenhui; Zhang, Ying (Frontiers in Psychology, 2020)
Three personality types (resilient, overcontrolled, and undercontrolled) have been repeatedly verified across different languages and cultures, different personality models, and different stages of development. Undercontrollers are socially maladapted types with high impulsivity and low self-control. Research shows they are at risk for externalizing problems, such as aggressiveness, impulsivity, and antisocial behavior. The aim of this study was to develop an intervention to reduce externalizing problems of undercontrolled personality types in primary school students. Participants were 69 undercontrolled primary school students from two primary schools in North China. The experimental group underwent 14 weeks of systematic experiential mental health activities, while the control group performed typical daily classroom activities. Personality and externalizing problem behaviors were measured before the intervention, at the end of the intervention, and 4 months post-intervention. The results showed that the intervention significantly reduced the level of externalizing problems of undercontrolled primary school students. The effects of the intervention were maintained at the 4-month follow-up. This study provides some reference and suggestions on how to intervene in the externalizing problem behaviors of undercontrolled primary school students.